PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM PENGGUNAAN OBAT-OBATAN KEDALUARSA - Dicky Handoko (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT Health is the most important thing that is needed by the human body. Efforts to improve the quality of life in the health sector constitute a very broad and comprehensive effort, including improving public health, both physical and non-physical. In the National Health System, the health of all aspects of life whose scope and scope is very broad and complex.The meaning of Article 1 paragraph (1) of Law Number 8 the Year 1999 concerning Consumer Protection formulates that consumer protection is an effort to ensure legal certainty to provide protection to consumers.BPOM Kota Samarinda further increases the intensity of the implementation of Prerentive and Repressive efforts to overcome the circulation of expired drugs in the community by paying attention to the negative aspects of Business Actors or Drug Producers in order to guarantee the health rights of consumers. Keywords: Consumers, expired drugs